1997
DOI: 10.1007/s003300050173
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial diffuse astrocytic tumours: proposal of an MRI classification

Abstract: The aim of this study was to obtain an MRI severity-related classification of diffuse astrocytic tumours able to integrate the histological data in the grading of such tumours. We studied presurgical MR images of 91 patients with a histological diagnosis of astrocytoma, anaplastic astrocytoma and glioblastoma. A score ranging from 1 to 3 was assigned by two independent readers to each of the following MR features: oedema, mass effect, contrast enhancement, borders, signal homogeneity, necrosis, haemorrhage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…Several studies found that MRIs of glioblastomas showed more hemorrhage, cyst formation, necrosis, and contrast enhancement than those of low-grade and anaplastic astrocytomas (18,19). The present report suggests that, with further volumetric analysis, a preoperative MRI may also enable prediction of molecular glioblastoma subtype.…”
Section: Mri Predictssupporting
confidence: 50%
“…Several studies found that MRIs of glioblastomas showed more hemorrhage, cyst formation, necrosis, and contrast enhancement than those of low-grade and anaplastic astrocytomas (18,19). The present report suggests that, with further volumetric analysis, a preoperative MRI may also enable prediction of molecular glioblastoma subtype.…”
Section: Mri Predictssupporting
confidence: 50%
“…Traditionally, the presence and degree of contrast enhancement (CE) after the administration of a gadolinium-based contrast agent on MR imaging have been used as characteristics of the malignancy of diffuse gliomas [4,5]. Typically, HGGs show moderate-to-strong CE, whereas LGGs exhibit no or mild CE.…”
Section: Introductionmentioning
confidence: 99%
“…The typical MR imaging features of low-grade astrocytomas include a relatively well-defined usually homogeneous mass that displays little or no mass effect, with minimal or no vasogenic edema and little or no enhancement after contrast administration. [5][6][7] Nevertheless, it is not always easy to differentiate low-grade astrocytomas from high-grade ones on the basis of conventional MR imaging findings. It has been reported that high-grade and low-grade astrocytomas can have overlapping features on MR imaging.…”
mentioning
confidence: 99%